Metode Problem Based Learning untuk Meningkatkan Hasil Belajar Siswa Pada Materi Pokok Bangun Ruang Sisi Lengkung - Umaro, Wardatul (FKIP Universitas Islam Jember, 2020)
Learning in the activity and education process. Researchers conducted observation in the class IX SMP Islam Tulupari and obtained data around 85% showing the same value date minus 70. The study aims student activity and the learning out comes in studying the wide and circumferential material incones with PBL models. The type of research used is a type or research into action. The procedure is a cycle I 65% for and cycle II 90%. While the result of the student’ daily tests on the cycle I 63.6% and the cycle 90.9%. This proves that learning activity and out comes increase with the creation of the PBL models. PBL learning is used to avoid boredom in learning.